TINJAUAN FIKIH WAKAF DAN UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF TERHADAP PENGELOLAAN WAKAF UANG OLEH YAYASAN TENDA VISI INDONESIA - Amrullah Hayatudin; Muhammad Andri Ibrahim; Ghina Nabila Ramadhanty (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
ABSTRACTToday many non-endowments institutions that receive and manage endowments of money include the Tenda Visi Indonesia Foundation (TEVIS). The TEVIS Foundation manages and distributes it according to its programs. So, this article was conducted by the author to find out the management of waqf money according to waqf fiqh and Indonesian Law Number 41 of 2004 concerning endowments, as well as the suitability of the management of endowments in money at the Tenda Visi Indonesia foundation with the concept of waqf money and Law No. 41 of 2004 concerning endowments. The method in this study is a qualitative method with a normative juridical approach, the type of research is field research using field data collection methods with observation, interviews, and also literature studies. The results of the study concluded that: first, the management of cash waqf according to fiqh only be distributed to what is permitted sharply according to law No. 41 of the management of cash waqf is carried out on banking products. Second, cash waqf management conducted by the TEVIS foundation is carried out in the real sector. Third, the management of cash waqf carried out by the TEVIS foundation was under fiqh waqf and according to Law No. 41 of 2004 concerning waqf, there is a discrepancy because of the TEVIS foundation doesn’t register its money to the minister and its management doesn’t go through banking product. Keywords: Fiqh of Waqf, Law No. 41 of 2004, Endowments of Money.